Step 1. Simplify 7/9(6x - 36) to 7(6x - 36)/9
23 = 7(6x - 36)/9 + 9
Step 2. Factor out the common term
23 = 7 * 6(x - 6)/9 + 9
Step 3. Simplify 7 * 6(x - 6) to 42(x - 6)
23 = 42(x - 6)/9 + 9
Step 4. Simplify 42(x - 6)/9 to 14(x - 6)/3
23 = 14(x - 6)/3 + 9
Step 5. Subtract 9 from both sides
23 - 9 = 14(x - 6)/3
Step 6. Simplify 23 - 9 to 14
14 = 14(x - 6)/3
Step 7. Multiply both sides by 3
14 * 3 = 14(x - 60
Step 8. Simplify 14 * 3 to 42
42 = 14(x - 6)
Step 9. Divide both sides by 14
42/14 to x - 6
Step 10. Simplify 42/14 to 3
3 = x - 6
Step 11. Add 6 to both sides
3 + 6 = x
Step 12. Simplify 3 + 6 to 9
9 = x
Step 13. Switch sides
x = 9